Pengaruh Faktor Keperilakuan Organisasi Terhadap Kegunaan Sistem Akuntansi Keuangan Daerah (Studi Kasus Di Dppkad Subosukawonosraten) - Janitra, Abdiel; , Dr Erma Setiawati SE. MM. Ak (2016)
This study aimed to examine the effect of behavioral factors Organization (supervisor support, clarity of purpose and training) of the Regional Financial Accounting System utilities. This study uses behavioral factors as the Organization of Independent Variables and Regional Financial Accounting System For Dependent Variables. The population is used as a sample is an employee in DPPKAD districts / cities in SUBOSUKAWONOSRATEN. This study uses a type of field research, with the type of data used are primary data obtained by distributing questionnaires to potential respondents on questions relating to the organization with Behavioral Factors Influence Of Regional Financial Accounting System utilities. The results showed that the behavioral organization (supervisor support, clarity of purpose and training) significantly affects the area of financial accounting system usability. To improve the usefulness of financial accounting system area then all those who are in authority need to realize the importance of the usefulness of the financial accounting system of the area, and the need to increase support supervisor, clarity of purpose and training that fully support in realizing the usefulness of financial accounting system area better within an agency.